Emerging Materials for Additive Manufacturing - Sing, Swee Leong; Yeong, Wai Yee (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In this reprint, state-of-the-art research and review articles on emerging material systems for additive manufacturing (AM) are collected, with a focus on the process-structure-properties relationships. Additive manufacturing (AM) has grown and evolved rapidly in recent years. There are many exciting research and translational works in many areas of application, such as biomedical, aerospace and electronics. These advancements are typically coupled with materials development, which has resulted in more functionalities added to 3D-printed parts, such as multi-material fabrications and integration with machine learning or digital twins. Such enhancements in functionalities have enabled the evolution of AM from a rapid prototyping tool to an actual manufacturing solution. In this reprint, two reviews and thirteen original research articles are included to highlight the latest development in the field of materials science for AM.